Trained immunity: a revolutionary immunotherapeutic approach - Md. Salauddin; Sabuj Kanti Nath; Sukumar Saha; Qingcong Zheng; Chunfu Zheng; Md. Golzar Hossain (BMC, 2024)
Abstract Trained immunity is a phenomenon in which brief exposure to an infectious agent or a vaccine can induce long-lasting changes in the host's immune system, enhancing protection against subsequent infections. The concept of trained immunity has a significant impact on the field of immunology and has the potential to revolutionize how we approach vaccination and infectious disease control. Investigations into trained immunity are rapidly advancing and have led to the development of new vaccines and immunotherapeutic strategies that harness the power of this phenomenon. While more investigations are needed to fully understand the mechanisms of trained immunity and its potential limitations, the prospects for its future application in clinical practice are promising. Here, we describe trained immunity as a biological process and explore the innate cues, epigenetic changes, and metabolic reprogramming activities that affect how trained immunity is induced.